BEARING CAPACITY OF STEEL I-SECTIONS UNDER COMBINED BENDING AND TORSION ACTIONS TAKING INTO ACCOUNT PLASTIC DEFORMATIONS - Tusnin, Aleksandr Romanovich; Prokic, Milan (Journal of Applied Engineering Science, 2014)
In steel structures, the I-beams are in many cases exposed to combination of bending moment and bimoment actions. In the elastic stage of work, material strength check is based on maximum normal stresses, which for symmetric I-beams are the sum of moment and bimoment stresses. The maximum stresses are compared with calculated resistance. In both European codes and Russian standards for design of steel structures, calculation of members is performed considering the conditions in which the plastic deformations over the section are allowed. With the development of plastic strains, bearing capacity of section is higher than in the elastic stage. The existing normative documents for the design of steel structures in Russia do not include design coefficient taking into account development of plastic deformations in warping torsion. The article examines combined action of bending moment and bimoment on I-beam profiles throughout the theoretical and numerical solutions. Recommendations for checking their bearing capacity in accordance to Russian standards are given, taking into account development plastic deformations.